A study on Effect of Surface Finishing Processes on Surface Roughness of AISI D2 Tool Steel (The International Journal of Engineering & Information Technology (IJEIT), 2024)
According to recent studies, dry hard turning is more beneficial practical process compared to a grindingoperation, it increases quality, reduces cost and lead-time formachined parts. In this study, effects of workpiece hardness,feed rate, depth of cut and cutting speed on surface roughnesswere studied using chamfered and honed CBN inserts. Fourfactors (hardness, depth of cut, feed rate and cutting speed)were considered and - two level fractional experiments wereconducted and analysis of the variance was performed.Furthermore this study shows that the effects of grinding ofheat treated AISI D2 specimens on surface roughness wereconducted and a comparison took place with hard turning. To investigate the effect temperature increase on bothtechniques, the machined surface of workpieces is examinedusing optical and scanning electron microscopy SEM.Practical results shows the lower workpiece hardness andlower cutting conditions resulted in a better surface roughness. Finally results showed that in hard machining not only themachining parameters have an influence on the surfaceroughness but also the material hardness found effective factorin finishing process.